Impact of polypharmacy on oral health status in elderly patients admitted to the recovery and rehabilitation ward. Issue 1 (6th December 2020) - Nakamura, Junya; Kitagaki, Kazufumi; Ueda, Yuya; Nishio, Eri; Shibatsuji, Takeshi; Uchihashi, Yasuyuki; Adachi, Ryohei; Ono, Rei
Abstract : Aim: The oral health status of elderly adults has implications for general health problems. Polypharmacy for elderly adults is associated with an increased risk of potentially inappropriate medicines and many adverse drug events; however, no report has shown that polypharmacy itself is associated with complex oral problems. This study aimed to determine the association between polypharmacy and oral health status in patients admitted to the recovery and rehabilitation ward. Methods: This cross‐sectional study included 471 patients (age: 81.9 ± 7.7 years, women: n = 346). Oral health status was measured using the Oral Health Assessment Tool and poor oral health status was defined as a score of ≥3. Cases of patients taking six or more medications were defined as polypharmacy. Logistic regression analysis was performed to examine the relationship between polypharmacy and oral health status. Age, sex, body mass index, number of comorbidities, cognitive and motor functions, and potentially inappropriate medicines were set as confounding factors. Results: Using the Oral Health Assessment Tool, 51.0% ( n = 240) of patients scored ≥3. The prevalence of patients with polypharmacy was 56.9% ( n = 268). Polypharmacy was significantly associated with poor oral health status (odds ratio = 1.65, 95% confidence interval = 1.14–2.39, P = 0.007; adjusted odds ratio = 1.65, 95% confidence interval = 1.12–2.43, P = 0.011). Conclusions: This study showed that polypharmacy was associated with poor oral health status. Focusing on the number of medications may be helpful in detecting oral problems. Geriatr Gerontol Int 2021; 21: 66–70 .